The influence of Corporate Governance Practices on Financial Performance of Small and Medium-Sized Enterprises in Ghana - Alhassan Musah; Abigail Padi (The Indonesian Journal of Accounting Research, 2022)
This study examined the influence of corporate governance practices on the financial performance of Small and Medium Sized Enterprises (SMEs) in Ghana. The study involved a survey of 320 owners/managers of SMEs through a stratified random sampling technique. The main instrument for the collection of data was a questionnaire whiles data was analysed using statistical tools such as mean and standard deviation as well as the use of multiple regression technique to answer the research questions. The results of the study showed that all the four areas of corporate governance practices examined in the study which include the size of the advisory board, the composition of the board, the managerial competence as well as financial disclosure and transparency were positively associated with financial performance of SMEs in Ghana. However, there is poor financial disclosure and transparency among SMEs in Ghana. Weak legal controls and law enforcement, and poor financial disclosure systems are some of the obstacles that affect the practice of corporate governance among SMEs. The study concludes that corporate governance practices of SMEs have significant impact on their financial performance. On the basis of the above findings and conclusion, it was recommended that shareholders of SMEs should ensure that their respective enterprises have active and sizeable advisory boards who meet regularly to support in the management of the firms. Also, managers of the firms should improve their managerial competence through training and development programmes as that affect performance of SMEs in Ghana